The clue in the embers - Dixon, Franklin W. (New York, Grosset & Dunlap, 1972)
In solving the mystery of two medallions missing from an inherited curio collection, the Hardys wind up in a desolate area of Guatemala at the mercy of dangerous thugs.
Keywords: Mystery and detective stories